Skrining Fitokimia dan Uji Toksisitas Ekstrak Daun Lamun Halophila Ovalis di Perairan Pantai Karma dan Pantai Serangan, Bali - Ramadhan, Rizky; Dirgayusa, I Gusti Ngurah Putra; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 7 No 2 (2021)DO - 10.24843/jmas.2021.v07.i02.p02, 2021)
Seagrass produced active compounds in a form of secondary metabolites as a survival system from predator attack and extreme environmental conditions. The active ingredient of seagrass extract can be an anticancer and antifungal. This study aimed to determine the content of active compounds and differences of toxicity level in seagrass extracts especially Halophila Ovalis in waters of Karma Beach and Serangan Beach. The method used for cytotoxicity test was Brine Shrimp Lethality Test (BSLT) using Artemia salina as an experimental animal. The result of phytochemical test showed that the extract of Halophila Ovalis leaf in Karma Beach contained bioactive compounds, such as alkaloids and tannins. Another side, the extract of Halophila Ovalis leaf in Serangan Beach contained 3 types of bioactive compounds, those were alkaloids, tannins and triterpenoids. The toxicity tests by BSLT method showed that the extract of Halophila Ovalis leaf in both research sites was non-toxic. The result was LC 50 where the LC 50 value of Halophila Ovalis leaf extract at the lowest to highest concentrations ie, (10, 100, and 1000 ug / ml) did not give a 50% mortality effect on Arthemi salina eggs.